Investigating the Dynamic Membrane Topology Of the Anti-Apoptotic Protein, Bcl-2, Using Cysteine Scanning Mutagenesis - Roberts, Gwendolyn (My University, 2005)
Bcl-2 proteins play a critical role in the regulation of apoptosis, a form of programmed cell death. Apoptosis is important during development to facilitate the elimination of supernumerary, damaged or harmful cells in multicellular organisms. Altered regulation of apoptosis is associated with many diseases such as several forms of cancer as well as autoimmune and degenerative disorders. The way in which Bcl-2 proteins regulate apoptosis is unknown and much research is focused on elucidating the molecular mechanism of their function. Bcl-2, an anti-apoptotic member of this family, is localized to the mitochondria, endoplasmic reticulum and nuclear envelope. In healthy cells, Bcl-2 adopts a typical tail-anchored topology in which the carboxyl-terminal helix (a9) is inserted into the membrane, anchoring the protein, leaving the majority of the protein in the cytosol. Previous results from our lab have shown that after the induction of apoptosis, Bcl-2 undergoes a conformational change in which the endogenous cysteine residue, C158, in the a5 helix becomes protected from a membrane impermeant cysteine specific labelling reagent, IASD (4-acetamido-4' ((iodoacetyl)amino)-stilbene-2,2'disulfonate). Modification of cysteine residues results in a change in migration ofBcl-2 in an isoelectric focusing, IEF, gel system. To investigate the nature of this conformational change, cysteine scanning mutagenesis was used to determine the topology of Bcl-2 in the late stages of apoptosis. The results from the current study showed that in rat 1 myc ERTM fibroblasts, a discontinuous sequence of residues in the a5 and a6 helices of Bcl-2 become protected from IASD labelling after the induction of apoptosis by etoposide or serum starvation. The data support a model topology in which, during apoptosis, Bcl-2 undergoes a functionally significant conformational change, going from a single spanning transmembrane protein to a polytopic membrane protein in which three helices span the membrane, a5, a6 and a9.
Keywords: Dynamic Membrane; Anti-Apoptotic; Protein; Cysteine Scanning; Mutagenesis